Analisis Perbandingan Politik, Ekonomi, Teknologi, Pertahanan Dan Keamanan Dan Sistem Pemerintahan 2 Negara Indonesia Dan Singapura - Brillianty, Reza Julieta (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
Indonesia and Singapore are countries with close geographical conditions, connected borders and alsohave a close historical background. The country of Singapore has a strategic position as a world traderoute, the drawback is the natural conditions that lack a variety of natural resources. Singapore andIndonesia are included in the continent of Southeast Asia, have a tropical climate. Comparison of political,economic, technological and defense and security systems compares two ormore countries in terms ofgovernment systems or others to find similarities or differences in one country and even many countries,because each country has its own form of government. Here the researcher compares two countries,namely Indonesia and Singapore. This research method is a qualitative research, namely to get a generalpicture of reality among various factors or various social phenomena that occur in people's lives. For thisreason, in this study a descriptive analysis method will be used which seeks to explain and describe indetail the object of research. As a result,the Indonesian state has similarities in the form of government,namely a republic, but it also has similarities in the economic system, technology and defense and security.